PENGARUH STRUKTUR ORGANISASI TERHADAP KUALITAS PELAYANAN PUBLIK (Suatu Studi Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Halmahera Utara) - PALIEMA, DESTRINA; Mandey, Jantje; Ogotan, Martha (Sam Ratulangi University, 2016)
Abstract: This study aimed (1) to describe the condition of the organizational structure and quality of publicservices in the Department of Population and Civil Registration Regency of North Halmahera. (2) to analyze theeffect of organizational structure on the quality of public services in the Department of Population and CivilRegistration North Halmahera Regency.This research uses descriptive method with quantitative approach. Samples were drawn by purposive sampling ofrespondents as many as 33 employees / personnel services, and 33 other respondents are elements of servicerecipients, then spread Questionnaire (questionnaire) and the results are analyzed by applying descriptivestatistical analysis techniques and simple regression analysis and correlation of product moment.Results of the study were presented as follows: (1) Organizational Structure Office of Population and Civil NorthHalmahera Regency is in the category